Possibilidades de emancipação : um estudo sobre o PBF, seu significado social e implicações - Figueiró, Sheila Farias (2009)
The present dissertation analyses the extent on which the Programa Bolsa Família can emancipate the individuals who participate in it and its social and economic significance to the beneficiary families. Its central problem is to investigate the current social policies, particularly the Bolsa Família, the purposes and objectives of the program. The research general objective is to verify on what extent these policies contribute on the processes of emancipation of the involved individuals. The social protection system is historically marked by the discontinuity of the social programs, however it is evident in the current context the expansion and advancement of the income transfer programs in order to reduce the high rates of poverty in the country. From these stands out the Bolsa Familia program which aims, among others, the possibility of human emancipation. Initially, the research treats about the relevant aspects of the family history and its insertion in the social policies context, prioritarily, the income transfer programs, highlighting a brief study of the Bolsa Família Program, presenting elements on its situation in the city of Marau / RS. The research is of documental and ethnographic nature, making use of structured interviews and applied to some beneficiary families from the program; it also used 250 records in order to draw a profile of the beneficiary families. Based on these elements, six families were chosen to be interviewed with semi-structured questions and the answers were analyzed highlighting the main issues and putted into perspective with the social reality and its meanings for families which are socially vulnerable. These, beyond the material poverty, have limitations in understanding the program policies, a factor that hinders the participation in activities related to this. However, those who can actively participate in the proposed social activities grow as autonomous individuals and evolve from spectators to protagonists of their own lives, breaking with the subordination and dependence and achieving human emancipation